Serum Concentration of Growth Differentiation Factor-15 Is Independently Associated with Global Platelet Function and Higher Fibrinogen Values in Adult Healthy Subjects - Lippi, Giuseppe; Salvagno, Gian Luca; Danese, Elisa; Brocco, Giorgio; Gelati, Matteo; Montagnana, Martina; Sanchis-Gomar, Fabian; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2017)
Growth differentiation factor-15 (GDF-15) has recently emerged as a strong and independent predictor of cardiovascular events and mortality. However, the pathophysiological mechanisms underlying this important association remain speculative. This study was aimed to investigate the potential associations between the serum concentration of GDF-15 and clinical or laboratory parameters in a population of ostensibly healthy subjects. The study population consisted of 44 healthy volunteers enrolled from the laboratory staff (14 males and 30 females; mean age, 47 ± 11 years), who had their blood collected for assessing complete blood cell count, GDF-15, serum creatinine, albumin, cardiac troponin T, galectin-3, routine coagulation tests, D-dimer, von Willebrand factor, and platelet function testing using platelet function analyzer-100. In univariate analysis, serum GDF-15 was found to be positively associated with age and plasma fibrinogen, and negatively associated with renal function and collagen-epinephrine (CEPI). In multiple linear regression analysis, serum GDF-15 remained significantly associated with renal function, CEPI, and plasma fibrinogen. Healthy subjects with GDF-15 above the median value had a twofold probability of displaying shorter CEPI closure times. Taken together, these results suggest that higher serum values of GDF-15 may be associated with overall global platelet hyperactivity and increased plasma fibrinogen, so providing another plausible explanation for the association between GDF-15, cardiovascular events, and mortality.
Keywords: growth differentiation factor-15; GDF-15; cardiovascular disease; platelets; PFA-100